New approaches to the development of human capital (Journal of Economic Research & Business Administration, 2024)
In the modern world, the increasing importance of human capital and the role of education in its formation is increasingly recognized. In educational practice, there is an underestimation of the possibilities of additional education, which does not allow children to fully reveal their potential. The purpose of the study is to develop recommendations that will help increase the level of enrollment of children in additional education.The purpose of the study is to develop recommendations to help increase the level of enrollment of children in additional education in order to develop human capital.The scientific and practical significance of the work lies in the fact that in the context of discussions about the contribution of education to the development of human capital, the importance of additional education for children and possible ways to more optimally organize this system are substantiated. During the study, formal logical methods and techniques were used. The main result of the study is that it highlighted not entirely obvious opportunities for the development of a system of additional education for children and measures were proposed to help increase the indicative indicator used in public administration - the level of enrollment of children in additional education. The value and practical significance of the study is expressed in the fact that, using the example of the central part of Almaty, a conceptually new approach to organizing additional education for children was proposed, which involves the creation of a system of additional school education that provides children with greater opportunities to unlock their potential during sensitive periods of development. At the same time, a model of an indicative map of the network of additional school education has been developed and proposed, promoting the formation of human capital at a qualitatively new level.Key words: additional education for children; human potential; human capital; accessibility of education; inclinations and abilities; talent; indicative map of the locality.